2004
DOI: 10.1002/pmic.200401026
|View full text |Cite
|
Sign up to set email alerts
|

Identification of target proteins of N‐acetylglucosaminyl‐transferase V and fucosyltransferase 8 in human gastric tissues by glycomic approach

Abstract: To understand better the mechanism underlying gastric cancer and search for potential markers for gastric cancer prognosis, the proteomic analysis of gastric cancer tissues was conducted using two-dimensional gel electrophoresis and lectin blot, followed by electrospray ionization-mass spectrometry. These approaches permitted identification of glyco- or putative glycosylated proteins which may be associated with tumorigenesis. The proteins identified include molecules involved in sugar metabolism, signal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…From the media protein samples were prepared and subjected to twodimensional electrophoretic analysis as described previously (12). For comparison of the expression level, 50 g of proteins was minimally labeled with cy3-or cy5-fluorescent dyes following two-dimensional differential in-gel electrophoresis, according to the manufacturer's instructions.…”
Section: Establishment Of Gnt-v and Timp-1 Transfectants-recombinantmentioning
confidence: 99%
See 1 more Smart Citation
“…From the media protein samples were prepared and subjected to twodimensional electrophoretic analysis as described previously (12). For comparison of the expression level, 50 g of proteins was minimally labeled with cy3-or cy5-fluorescent dyes following two-dimensional differential in-gel electrophoresis, according to the manufacturer's instructions.…”
Section: Establishment Of Gnt-v and Timp-1 Transfectants-recombinantmentioning
confidence: 99%
“…For this, we adopted proteomics and glycomics techniques in which two-dimensional electrophoresis, lectin blot analysis, and MS-based protein identification were linked. We have previously reported that these approaches allowed us to identify several candidate proteins that are assumed to be involved in progressions of gastric cancer (12) and colon cancer (13) and have validated these approaches for discovery of biomarker by showing the role of aberrant glycosylation of protein tyrosine phosphatase as an example in cancer cell migration (13). In this article, we report that additional candidate proteins were identified including tissue inhibitor of metalloproteinase-1 (TIMP-1) as the target for GnT-V and, more importantly, that the aberrant glycosylation of TIMP-1 is closely correlated with invasive/metastatic potential of colon cancer cell WiDr.…”
mentioning
confidence: 99%
“…2-DE, dating back to the 1970s [10,11] , in conjunction with MS, has allowed the identification of differentially expressed proteins in various diseases, including GC [12][13][14][15][16][17] . However, the process of translating basic proteomic discoveries to the clinic is very time consuming and expensive, and despite all the efforts put into biomarker research, very few diagnostic protein biomarkers have been approved by the United States Food and Drug Administration [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Glycoproteome is also a major subproteome: many clinical biomarkers and therapeutic targets are glycoproteins. In particular, the glycosylation patterns are influenced considerably by the physiological status (Kim et al, 2004;Zhao et al, 2006). Therefore, in this study, a differential glycoprotein profiling of plasma trials of healthy donors and AD patients was performed.…”
Section: Introductionmentioning
confidence: 99%